2003
DOI: 10.1136/oem.60.9.667
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between hearing thresholds measured in non-soundproof work environments and a soundproof booth

Abstract: Aims: To study the agreement between audiometric test results measured in non-soundproof environments at the worksite, and in a soundproof booth. Methods: In a cross sectional prevalence study on noise induced hearing loss, 885 transport workers whose hearing thresholds were measured by a standard audiometric test method in non-soundproof environments at the worksite were identified to have some hearing loss (>25 dB), and were retested in a soundproof booth. Results: At 4-8 KHz, the mean of the absolute differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…Research carried out by Wong et al (25) highlighted that low frequency ambient noise levels result in the increased variance of hearing thresholds for the lower frequencies with higher frequencies being less affected, findings consistent with current findings. Research carried out by Wong et al (25) highlighted that low frequency ambient noise levels result in the increased variance of hearing thresholds for the lower frequencies with higher frequencies being less affected, findings consistent with current findings.…”
Section: Discussionsupporting
confidence: 90%
“…Research carried out by Wong et al (25) highlighted that low frequency ambient noise levels result in the increased variance of hearing thresholds for the lower frequencies with higher frequencies being less affected, findings consistent with current findings. Research carried out by Wong et al (25) highlighted that low frequency ambient noise levels result in the increased variance of hearing thresholds for the lower frequencies with higher frequencies being less affected, findings consistent with current findings.…”
Section: Discussionsupporting
confidence: 90%
“…[42] At the same time, it was demonstrated that when the exposure to harmful levels of noise was interrupted, the significant progression of NIHL was detained. [2] In this sense, the study of the workday distribution is an especially important issue for some authors, particularly about the duration and frequency of the nonexposure periods between work turns. [11]…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, noise, defined as undesirable sound, in one of the most common hazards at occupational and environmental level,[2] and sound level exceeding 85 dB is harmful to health; this effect is further increased depending on the duration and systematic exposure,[3] as well as the intensity and frequency of the sound,[4] the risk factors among the exposed population, the individual susceptibility, ethnicity,[5] sex,[6] and the exposure to other physical,[7] chemical,[8910] and biological[9] agents.…”
Section: Introductionmentioning
confidence: 99%
“…Care was taken so that there was no external noise by closing all the doors and windows of the room and requesting the people around the room to maintain silence until the procedure was completed. Ambient noise was measured at the beginning of audiometry using decibelometer and ensured that it was below 30 dB [21]. Measured hearing loss was determined using pure tone audiometry, intensity of sound was measured in decibels, and both degree and type of deafness were assessed.…”
Section: Methodsmentioning
confidence: 99%